Soekarno's Critique of the Fiqh Model in Traditional Pesantren - Kurniawan, Syamsul; Fitriyani, Feny Nida; Miftah, Muhammad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
This article discusses the fiqh learning model of traditional pesantren which according to Soekarno is a very old-fashioned and does not follow the spirit of the times, tends to be shackling, dichotomous, and has not placed religion and science in a balanced position. As a result of the fiqh taught in traditional dichotomous pesantren, santri are less able to adapt to change. The reason is because they learn fiqh that tends to: one, limit it to matters relating to worship to God and how to build relationships with fellow humans only, while the outside of this is not a priority; two, not built on scientific reasoning; three, perspectives that are mostly rigid (black and white); and four, teaching patterns that tend to be indoctrination and anti-criticism. This article is important to reveal Soekarno's criticism of the fiqh model in traditional pesantren, which still exists today. This type of study is a literature study whose data is obtained from literature studies. This study also can be classified in the category of historical-factual studies, while in terms of its approach, this study is qualitative, while the method is descriptive-interpretative with content, language, and concept analysis models, especially to discuss what Soekarno criticised in relation to the fiqh model in traditional pesantren.